PELATIHAN PENANAMAN PADI MENGGUNAKAN METODE JAJAR LEGOWO DI NAGARI SUNGAI DAREH KECAMATAN PULAU PUNJUNG KABUPATEN DHARMASRAYA - Suhendra, Dede; Edwin, Edwin; Sari, Wulan Kumala; Rezki, Dewi; Heriza, Sri; Yulistriani, Yulistriani; Ikhsan, Zahlul; Karjunita, Nike; Hasibuan, Halimatus Syahdia; Wisnubroto, Muhammad Parikesit (Jurnal Hilirisasi IPTEKS, 2024)
Rice is a primary necessity for the Indonesian people, as it serves as a source of energy and carbohydrates. Rice cultivation requires strategic approaches to increase production, aiming to prevent threats to Indonesia's food security. One strategy that can be applied is the jajar legowo rice planting system. The jajar legowo system is a technique that manipulates planting distances to increase rice yields, resulting in a greater number of edge plants. This activity aims to enhance farmers' understanding of rice cultivation using the jajar legowo system to achieve better harvests and to boost their enthusiasm in working on their agricultural land. The activity was conducted on the rice fields owned by the Tanjung Raya farming group, located in Nagari Sungai Dareh, Pulau Punjung District, Dharmasraya Regency. The method employed involved directly practising the jajar legowo rice planting system in the farmers' rice fields. The activity proceeded smoothly, successfully increasing the farmers' understanding of *jajar legowo* rice cultivation to achieve better harvests. Both the farmers and students involved in the activity were able to perform their tasks according to the specified guidance. Looking forward, it is hoped that similar activities will be held, as this initiative by the students of Campus III Universitas Andalas Dharmasraya aims to provide benefits and positive contributions to the surrounding community.